Poverty and Shared Prosperity : Let's Move the Discussion Beyond Growth - Antoine, Kassia; Singh, Raju Jan; Wacker, Konstantin M. (Taylor and Francis, 2017)
Some authors argue that it is enough to focus on growth to achieve lower poverty and greater shared prosperity. Policy-makers are warned that any effort to make growth more equal would be a distraction at best and could even be detrimental. Achieving the World Bank target of a 3% poverty rate by 2030 will require, however, more targeted policies favoring the poorest segments of the population. But what would be these policies? While studies investigating determinants of GDP growth have been numerous, less is known about factors influencing household incomes at the lowest segments of the income distribution. This paper estimates income drivers for the poorest two income quintiles drawing on a panel of 117 countries over the period 1967–2011. Its results suggest that maintaining macroeconomic stability as well as investing in human and physical capital would not only be associated with faster overall economic growth, but also with even faster income growth for the poorest segments of the population. This paper confirms the central role overall economic growth should play in any strategy to reduce poverty. Its results suggest, however, that in addition policy-makers may have instruments to tweak the distribution of the benefits of faster economic growth in favor of the households at the bottom of the income distribution. There thus need not be a trade-off between inequality and growth.